PENINGKATAN KETERAMPILAN MEMBACA INTENSIF MENGGUNAKAN PENERAPAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) PADA SISWA KELAS IX-1 SMP NEGERI 2 BUNTU PANE SATU ATAP - Kholipah, Siti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The subjects of the study were teachers and students of class IX-1 of the Middle School 2 Buntu Single Roof Pane which numbered 33 students, there were two types of data namely quantitative and qualitative data.The data collection techniques used were test techniques using instruments in the form of non-test questions and techniques in the form of observation sheets, interview sheets and field notes the data used is the analysis of quantitative and qualitative data. The results showed that teacher skills, student activities and learning outcomes in intensive reading learning with the CIRC model increased. The teacher's skills in the first cycle got an average score of 78.48, the second cycle of the average score was 82.57. The activity of students in the first cycle, got the value of completeness of classical learning outcomes in the first cycle 84.84%, and the second cycle 96.96%. The conclusion of this study is that the application of the CIRC model can improve teacher skills, student activities and student learning outcomes in the form of intensive reading skills can be improved.